Clusters of circulating tumor cells: A biophysical and technological perspective. (September 2017) - Au, Sam H.; Edd, Jon; Haber, Daniel A.; Maheswaran, Shyamala; Stott, Shannon L.; Toner, Mehmet
Abstract: The vast majority of cancer associated deaths result from metastasis, yet the behaviors of its most potent cellular driver, circulating tumor cell clusters, are only beginning to be revealed. This review highlights recent advances to our understanding of tumor cell clusters with emphasis on biophysics and enabling technologies. A number of strategies for isolating these clusters from patient blood have enabled studies aimed at unraveling the importance of intercellular adhesions in cluster metastasis. Furthermore, due to their metastatic potency, the utility of circulating tumor cell clusters for cancer diagnosis, drug screening, precision oncology and as targets of antimetastatic therapeutics are currently being explored. The continued development of tools for isolating and understanding circulating tumor cell clusters will enhance our fundamental understanding of the metastatic process and may be instrumental in devising new strategies to suppress and eliminate metastasis.